Comparative foliar anatomical and pollen morphological studies of Acanthaceae using light microscope and scanning electron microscope for effective microteaching in community. Issue 9 (8th July 2020) - Raza, Jamil; Ahmad, Mushtaq; Zafar, Muhammad; Athar, Mohammad; Sultana, Shazia; Majeed, Salman; Yaseen, Ghulam; Imran, Muhammad; Nazish, Moona; Hussain, Amir
Abstract: In this study, foliar anatomy and pollen morphology of 10 species of Acanthaceae has been investigated using light and scanning electron microscopy. The study was aimed to highlight the role of microscopy in microteaching at community for proper characterization of plants using palyno‐anatomical characters including pollen type, exine sculpturing, shape of epidermal cells, pattern of anticlinal wall, type and size of stomata, and trichome. Most of the species have polygonal cell shapes but some species have irregular, tetragonal, and pentagonal shape of epidermal cells. The largest epidermal cell length on adaxial and abaxial surface were observed in Asystasia gangetica 66.95 and 87.40 μm whereas least was observed on adaxial surface in Justicia adhatoda 36.9 μm and on abaxial surface in Barleria cristata 35.65 μm. In anatomy, species have diacytic type of stomata, whereas stomata of paracytic type observed in two species, while in A. gangetica cyclocytic type of stomata are present. Quantitively on abaxial surface, largest stomata length 29.9 μm and width 24.30 μm was noted in B. cristata . While shortest stomata length was observed in Ruellia prostrata 25.95 μm whereas minimum width of stomata was examined in Barleria acanthoides 2.05 μm. The diversity of trichomes are present in all species except in Ruellia brittoniana . Acanthaceae can be characterized by exhibiting different pollen morphology having five types of pollen shapes, prolate, spheroidal, perprolate, subprolate, and oblate spheroidal. Exine peculiarities showing variations such as reticulate, granulate, coarsely reticulate, lophoreticulate, perforate tectate, and granulate surface were examined. Abstract : Highlights Description of foliar anatomy and pollen morphology of family Acanthaceae There is a highly variation in palyno‐anatomical characters. Diversification in leaf epidermal cell shapes among species Pollen morphology has play important taxonomic role in the identification of Acanthus species